Sonate en si bemol par Beethoven op: 22 ; revus, doigtés et accentués par Marmontel - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Marmontel, Antoine François, 1816-1898 (editor):::Contributor:::::::::::: (France; Heugel et Cie.; Paris, 2023)
Mid ninteenth-century edition of the Piano Sonata no. 11 in B-flat major, op. 22, edited by Antoine François Marmontel for the series "Chefs-d'oeuvre classique pour le piano" published by Heugel & Cie. in Paris.